DISTANCE CONTROL OF PATIENTS REHABILITATION PROCESSES - Mintser, O. P.; Shevtsova, O. M.; Sarkanych, O. V. (Medical Informatics and Engineering, 2020)
Background. Remote health issues, especially the problems of identifying patients with information technology outside the inpatient setting, are addressed. Materials and methods. Results. The purpose of the study is to substantiate systemic solutions in technologies for the use of remote management of patient rehabilitation. It is concluded that the current level of interpretation of patient information is insufficient to detect similarity and classification into clinically based groups on the spectrum of symptoms, signs, biomarkers, and to understand how to use this data for stratification of patients. Rehabilitation oriented ontology is offered, which provides necessary explanations and provides opportunities for personalization of diagnosis and treatment of patients, based on structural links between clinical concepts in ontology. Conclusion. Remote provision of medical care is possible subject to appropriate conceptualization, based on the principles of justification for stable states, trigger-cascade representations, and use of ontology of knowledge.